NUTRITIONAL VALUE OF PROTEINS FROM WHEAT BRAN IN BAKERY PRODUCTS - Qodiraliyeva, H.G.; Amanov, B.N.; Iskandarova, Sh. M.; Rahimova, M.Z.; Nurmatov , J.J. (Innovative Development in Educational Activities, 2024)
In order to create food products with controlled composition and nutritional properties for the production of protein products, it is advisable to use raw materials that actually exist in the country - wheat bran. In terms of water-binding capacity, bran protein flour is close to full-fat soy flour and surpasses all other protein products in this indicator (1.3-5.3 times). Protein products from bran have a high fat-binding ability to form an “oil in water” emulsion. Along with the ability to change the surface tension at the oil-water interface, bran protein products had a similar property in relation to the gas-water phases.